Analisis Penggunaan Radiasi Pengion untuk Pemanfaatan Pertumbuhan Buah dan Sayur di Indonesia - Fauziah, Najma Zahiroh; Nanda Wulandari, Meri; Gea Alivia Putri, Miftahul; Sudarti; Mahmudi, Kendid (Fakultas Pertanian, Program Studi Agroteknologi, 2024)
Abstract In Indonesia, there are many people who have difficulty in preserving vegetables. Especially in the agricultural industry when after harvesting, ensuring that the processed raw materials are free from spoilage microorganisms. With the development of the times, it appears to minimize the occurrence of decay in vegetables by ionizing radiation or ionizing radiation is radiation that causes ionization while non-ionizing radiation is radiation that does not cause ionization. The research method used is a literature study which is a series of data collection techniques, processing data from previous researchers that are relevant to the theme that has been made. In the process of preventing spoilage is done by means of ionizing radiation or ionizing radiation by utilizing gamma rays. Proven from several studies of chili plants, rice plants, soybean plants, and several other vegetables proving ionizing radiation or ionizing radiation that utilizes gamma rays in the process can help maintain vegetable quality after post-harvesting vegetables and fruits.